2020
DOI: 10.3847/1538-4365/ab65bd
|View full text |Cite
|
Sign up to set email alerts
|

Density Fluctuations in the Solar Wind Based on Type III Radio Bursts Observed by Parker Solar Probe

Abstract: Radio waves are strongly scattered in the solar wind, so that their apparent sources seem to be considerably larger and shifted than the actual ones. Since the scattering depends on the spectrum of density turbulence, better understanding of the radio wave propagation provides indirect information on the relative density fluctuations = δn / n at the effective turbulence scale length. Here, we have analyzed 30 type III bursts detected by Parker Solar Probe (PSP). For the first time, we have retrieved type III b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 40 publications
14
76
0
Order By: Relevance
“…Therefore, we do not discuss the geometric radio source sizes, but only the radio source regions as defined above. A Similar procedure was used in previous studies (Reiner et al 1998;Martínez Oliveros et al 2012b;Martínez-Oliveros et al 2015;Mäkelä et al 2016Mäkelä et al , 2018Krupar et al 2020) • The estimated distance between the two wave vectors is generally smaller at high frequencies. Hence, In this analysis we used the highest available frequencies of direction finding observations, and we did not use frequencies below 500 kHz.…”
Section: Radio Triangulationmentioning
confidence: 97%
“…Therefore, we do not discuss the geometric radio source sizes, but only the radio source regions as defined above. A Similar procedure was used in previous studies (Reiner et al 1998;Martínez Oliveros et al 2012b;Martínez-Oliveros et al 2015;Mäkelä et al 2016Mäkelä et al , 2018Krupar et al 2020) • The estimated distance between the two wave vectors is generally smaller at high frequencies. Hence, In this analysis we used the highest available frequencies of direction finding observations, and we did not use frequencies below 500 kHz.…”
Section: Radio Triangulationmentioning
confidence: 97%
“…In-situ (Celnikier et al 1983;Krupar et al 2020) and remote-sensing radio observations (Wohlmuth et al 2001) suggest that the density fluctuations in the interplanetary space have an inverse power-law spectrum S(q) ∝ q −(p+2) , with the spectral index p close to 5/3. The power-law is normally observed over a broad inertial range, from the outer scales l 0 = 2π/q 0 to the inner scales l i = 2π/q i , so we consider…”
Section: Equationsmentioning
confidence: 99%
“…The grey-shaded area represents the decay time of the burst observed by LOFAR. Krupar et al (2020)). The one standard deviation uncertainty calculated during fitting is used as the error in the measurements of decay time.…”
Section: Fundamental Emissionmentioning
confidence: 99%
“…Hollweg, Cranmer, and Chandran (2010), evaluating a wave-heating model based on Helios data, showed ∼ 0.023 -0.031 at SO 2R , and rising an order of magnitude by SO 20R . Krupar et al (2018) evaluated density fluctuations from type III radio bursts measured by STEREO spacecraft, and more recently Krupar et al (2020) gave results from the Parker Solar Probe first and second perihelia. Both studies revealed fractional density fluctuation of 0.06 -0.07 in the extended corona.…”
Section: Assignment Of Parametersmentioning
confidence: 99%